Protein surface engineering and interaction studies of maltogenic amylase towards improved enzyme immobilisation - TOKSOY ÖNER, EBRU (My University, 2022)
A combined strategy of computational, protein engineering and cross-linked enzyme aggregates (CLEAs) approaches was performed on Bacillus lehensis G1 maltogenic amylase (Mag1) to investigate the preferred amino acids and orientation of the cross-linker in constructing stable and efficient biocatalyst. From the computational analysis, Mag1 exhibited the highest binding affinity towards chitosan (-7.5 kcal/mol) and favours having interactions with aspartic acid whereas glutaraldehyde was the least favoured (-3.4 kcal/mol) and has preferences for lysine. A total of eight Mag1 variants were constructed with either Asp or Lys substitutions on different secondary structures surface. Mutant Mag1-mDh exhibited the highest recovery activity (82.3%) in comparison to other Mag1 variants. Mutants-CLEAs exhibited higher thermal stability (20-30% activity) at 80 C whilst Mag1-CLEAs could only retain 9% of activity at the same temperature. Reusability analysis revealed that mutants-CLEAs can be recovered up to 8 cycles whereas Mag1-CLEAs activity could only be retained for up to 6 cycles. Thus, it is evident that amino acids on the enzyme\"s surface play a crucial role in the construction of highly stable, efficient and recyclable CLEAs. This demonstrates the necessity to determine the preferential amino acid by the cross-linkers in advance to facilitate CLEAs immobilisation for designing efficient biocatalysts.
Keywords: Yaşam Bilimleri; Moleküler Biyoloji ve Genetik; Sitogenetik; Kimya; Fizikokimya; Polimer Karakterizasyonu; Diğer; Temel Bilimler; Life Sciences; Molecular Biology and Genetics; Cytogenetic; Chemistry; Physical Chemistry; Characterization of Polymers; Other; Natural Sciences; BİYOKİMYA VE MOLEKÜLER BİYOLOJİ; Moleküler Biyoloji ve Genetik; Yaşam Bilimleri (LIFE); KİMYA, UYGULAMALI; Temel Bilimler (SCI); POLİMER BİLİMİ; BIOCHEMISTRY & MOLECULAR BIOLOGY; MOLECULAR BIOLOGY & GENETICS; Life Sciences (LIFE); CHEMISTRY, APPLIED; CHEMISTRY; Natural Sciences (SCI); POLYMER SCIENCE; Biyokimya, Genetik ve Moleküler Biyoloji (çeşitli); Klinik Biyokimya; Kanser Araştırmaları; Moleküler Biyoloji; İlaç Keşfi; Yaşlanma; Genel Biyokimya, Genetik ve Moleküler Biyoloji; Biyokimya; Yapısal Biyoloji; Polimerler ve Plastikler; Kimya (çeşitli); Genel Kimya; Proses Kimyası ve Teknolojisi; Fizik Bilimleri; Biochemistry, Genetics and Molecular Biology (miscellaneous); Clinical Biochemistry; Cancer Research; Molecular Biology; Drug Discovery; Aging; General Biochemistry, Genetics and Molecular Biology; Biochemistry; Structural Biology; Polymers and Plastics; Chemistry (miscellaneous); General Chemistry; Process Chemistry and Technology; Physical Sciences; Computational analysis; Protein engineering; Enzyme immobilisation; Protein orientation; Protein secondary structure; HETEROFUNCTIONAL CARRIER; COVALENT IMMOBILIZATION; CANDIDA-RUGOSA; STABILITY; LIPASE; ORIENTATION; STRATEGIES; SUPPORTS; SITE; BENTONITE